STUDI KINETIKA REAKSI EKSTRAKSI DOLOMIT DENGAN ASAM FOSFAT - Fahturrozak, Ahmad; Adzani, Mayla Fayzza; Sumada, Ketut (Universitas Nahdlatul Ulama Blitar, 2026)
Dolomite (CaMg(CO₃)₂) is generally white but can also appear gray or bluish, with magnesium (Mg) and calcium (Ca) as its main composition.. This study analyzes the kinetics and conversion of dolomite extraction using phosphoric acid through a solid-liquid extraction method. Initially, dolomite was calcined at 850°C for 240 minutes and then sieved. A total of 40 grams of the sieved sample was extracted with 250 mL of 2M phosphoric acid at varying temperatures (30, 45, 60, 75, and 90°C) and extraction times (60, 90, 120, 150, and 180 minutes). The extracted solution was filtered and analyzed using AAS to determine the extracted calcium and magnesium content. The highest conversion was achieved at 90°C for 180 minutes, with calcium extraction at 65.67% and magnesium at 65.98%, with the ash layer as the controlling step. The activation energy, based on the Arrhenius equation, was 27,745.49 J/mol·K for calcium and 19,120.5 J/mol·K for magnesium, with reaction rate constants of K=9.8149 e^(3336.6/T) for calcium and K=1.8063 e^(2299.8/T) for magnesium. This study demonstrates that temperature and reaction time significantly influence dolomite extraction, which follows the Arrhenius model, providing valuable insights into the kinetics and efficiency of dolomite extraction using phosphoric acid.